2015
DOI: 10.4172/1948-5956.1000358
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Biofield Treatment on Cancer Biomarkers Involved in Endometrial and Prostate Cancer Cell Lines

Abstract: Increasing cancer rates particularly in the developed world are associated with related lifestyle and environmental exposures. Combined immunotherapy and targeted therapies are the main treatment approaches in advanced and recurrent cancer. An alternate approach, energy medicine is increasingly used in life threatening problems to promote human wellness. This study aimed to investigate the effect of biofield treatment on cancer biomarkers involved in human endometrium and prostate cancer cell lines. Each cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 37 publications
1
108
0
Order By: Relevance
“…Antimicrobial interactions with S. marcescens might alter the ligand-receptor protein that results in different phenotypic characteristics [34]. Our research group has also reported significantly improved the sensitivity pattern of antibiotics after biofield treatment on pathogenic microbes [19,20], and inhibit the growth of cancer cells [35]. The results are very well supported with previous published literature.…”
Section: Antimicrobial Susceptibility Testsupporting
confidence: 85%
“…Antimicrobial interactions with S. marcescens might alter the ligand-receptor protein that results in different phenotypic characteristics [34]. Our research group has also reported significantly improved the sensitivity pattern of antibiotics after biofield treatment on pathogenic microbes [19,20], and inhibit the growth of cancer cells [35]. The results are very well supported with previous published literature.…”
Section: Antimicrobial Susceptibility Testsupporting
confidence: 85%
“…The biofield energy treatment is effectively used to stimulate the overall health of human being by reducing the pain and anxiety [23,24]. Mr. Trivedi is well known for his unique biofield energy treatment (The Trivedi Effect ® ) that has been evaluated in numerous arenas like agricultural research [25], biotechnology research [26], microbiology research [27,28], pharmaceutical sciences [13,19], and materials science [29,30].…”
Section: Insights In Analytical Electrochemistrymentioning
confidence: 99%
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23][24][25], nutraceuticals [26,27], organic compounds [28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate exhibits the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%